Bmp4 regulates chick Ebf2 and Ebf3 gene expression in somite development. (23rd September 2013) - El‐Magd, Mohammed A.; Allen, Steve; McGonnell, Imelda; Otto, Anthony; Patel, Ketan
<x xml:space="preserve">Abstract</x> The chick Early B‐cell Factor‐2 and 3 (cEbf2 and cEbf3) genes are members of EBF family of helix loop helix transcription factors. The expression, regulation and importance of these genes have been extensively studied in lymphatic, nervous and muscular tissues. Recently, a new role for some members of EBF in bone development has been investigated. However, the expression profile and regulation in the axial skeleton precursor, the somite, have yet to be elucidated. Therefore, this study was aimed to investigate the expression and regulation of cEbf2 and cEbf3 genes in the developing chick embryo somite from HH4 to HH28. The spatiotemporal expression study revealed predominant localization of cEbf2 and cEbf3 in the lateral sclerotomal domains and later around vertebral cartilage anlagen of the arch and the proximal rib. Subsequently, microsurgeries, ectopic gene expression experiments were performed to analyze which tissues and factors regulate cEbf2 and cEbf3 expression. Lateral barriers experiments indicated the necessity for lateral signal(s) in the regulation of cEbf2 and cEbf3 genes. Results from tissue manipulations and ectopic gene expression experiments indicate that lateral plate‐derived Bmp4 signals are necessary for the initiation and maintenance of cEbf2 and cEbf3 genes in somites. In conclusion, cEbf2 and cEbf3 genes are considered as lateral sclerotome markers which their expression is regulated by Bmp4 signals from the lateral plate mesoderm.